STUDI PADA PROGRAM KEMITRAAN PERUM PERIKANAN INDONESIA (PERINDO) TERHADAP MASYARAKAT PESISIR PANTAI YANG BERMATA PENCAHARIAN NELAYAN (Studi Kasus di Pelabuhan Perikanan Samudra Pantai Prigi,Kecamatan Watulimo,Trenggalek) - Wahyu Eko Sasmito (Universitas Negeri Malang, 2014)
The wealth of Indonesia's marine resources are very abundant, following the two- thirds of Indonesia consists of marine, fishery potential as much as 6.26 million tons/year with a diversity of fish species but not yet fully exploited today optimal. But the problems arise quite complicated hit fishermen like a decrease in the quality of the catch and the high losses rate. answer this problem fisheries Indonesia Perum PERINDO. emerged as the company services and supporting infrastructure provider in the field of ocean fisheries. This study to determine the determine the extent of the contribution of business partnership program Perum PERINDO in helping coastal communities as a whole to overcome the problems in an effort to improve their economic enterprises.